(untitled) (Brazilian Journal of Oceanography, 2008)
In marine fouling communities, free space is one of the key limiting resources for settlement of new organisms. In this way, removing biomass through physical disturbances would play an important role in the structure and dynamics of these communities. The disturbance size seems to be a characteristic that influences recolonization patterns, thus affecting species diversity. The aim of this study was to analyze the effects of growing disturbance areas on fouling communities. Fouling panels were allowed to develop for 6 mo. at Guanabara Bay (22°52'S, 043°08'W) prior to a single application of randomly positioned, circular physical disturbances of growing areas (7 levels, from 0 to 75% removed cover, 10 replicates per treatment). Samples were taken fortnightly after the disturbance event, so as to follow the development patterns of the community afterward. At the first sampling the diversity showed maximum indices in communities to which intermediary disturbance levels were applied. However, this profile changed later to a diversity peak in communities with higher disturbance levels. It also showed a continuous increase in richness and diversity through time until the 7th sample (110 days after the disturbance event), with subsequent decrease. Such patterns seem to corroborate the Intermediate Disturbance Hypothesis, despite the drastic profile change with time, revealing that disturbance is indeed an important factor structuring hard bottom communities at Guanabara Bay, and highlighting the importance of longer term studies of disturbance impacts in marine communities.